Thermoregulatory behavior applied to the culture of Procambarus clarkii (Decapoda: Cambaridae) - Bückle R., L Fernando (1996)
In thermoregulatory behavior of Procambarus clarkii studied on organisms acclimated to 20, 23, 26 and 29 "C, body mass did not affect tolerance and resistance. Acclimation temperatures exerted no significant influence on the preferred temperatures nor on the final preferendum (23.4 oC). Nevertheless, acclimation positively affected the low temperature avoidance threshold: the upper incipient lethal temperature by 0.6 oC and the critical thermal maximum (CTM), by 3.2 oc. When culturing P. clarkii in Baja California, temperature should be close to the final preferendum, and within the accepted range of 16.9 - 28.5 oC.